Pengaruh Pertumbuhan Ekonomi, Pendidikan dan Kesehatan Terhadap Tingkat Kemiskinan di Kabupaten Kupang - Frederikus Roky Ikwan Soko; Fransina Wely Ballo (RJABM (Research Journal of Accounting and Business Management), 2023)
This study aims to explain the effect of economic growth, education and health on poverty levels in Kupang District. This research is a quantitative study with time series data for 21 years, namely during the 2002-2022 observation period. The data used are data on the growth rate of gross regional domestic product at constant prices of 2000 and 2010, mean years of schooling data and life expectancy data from the Central Statistics Agency of Kupang Regency. The analytical method used is multiple linear regression analysis which is processed through Eviews-12 software. The results of this study show that partially the economic growth and education variables have no effect on the poverty rate in Kabupaten Kupang. Meanwhile, the health variable has a significant effect on the poverty rate in Kupang Regency, this is because development in the health sector in Kupang Regency has shown positive developments, which means that the quality of public health and community work productivity has also increased. Simultaneously, economic growth, education and health variables have a significant effect on the poverty rate in Kabupaten Kupang.